RuBPCase activase mediates growth-defense tradeoffs: Silencing RCA redirects JA flux from JA-Ile to MeJA to attenuate induced defense responses in Nicotiana attenuata - Mitra, Sirsha (New Phytol, 2013)
RuBPCase activase (RCA), an abundant photosynthetic protein is strongly down-regulated in response to Manduca sexta’s oral secretion (OS) in Nicotiana attenuata. RCA-silenced plants are impaired not only in photosynthetic capacity and growth, but also in jasmonic acid (JA)-isoleucine (Ile) signaling, and herbivore resistance mediated by JA-Ile dependent defense traits. These responses are consistent with a resource-based growth-defense trade-off. Since JA+Ile-supplementation of OS restored WT levels of JA-Ile, defenses and resistance to M. sexta, but OS supplemented individually with JA- or Ile did not, the JA-Ile deficiency of RCA-silenced plants could not be attributed to lower JA or Ile pools or JAR4/6 conjugating activity. Similar levels of JA-Ile derivatives after OS elicitation indicated unaltered JA-Ile turnover and lower levels of other JA-conjugates ruled out competition from other conjugation reactions. RCA-silenced plants accumulated more methyl jasmonate (MeJA) after OS elicitation, which corresponded with increased jasmonate methyltransferase (JMT) activity. RCA-silencing phenocopies JMT over-expression, wherein elevated JMT activity redirects OS-elicited JA flux towards inactive MeJA, creating a JA sink which depletes JA-Ile and its associated defense responses. Hence RCA plays an additional non-photosynthetic role in attenuating JA-mediated defenses and their associated costs potentially allowing plants to anticipate resource-based constraints on growth before they actually occur.